Narcolepsy: clinical differences and association with other sleep disorders in different age groups - Nevsimalova, Sona; Pisko, Juraj; Buskova, Jitka; Kemlink, David; Prihodova, Iva; Sonka, Karel; Skibova, Jelena (Journal of neurology, 2013)
Narcolepsy-cataplexy (N-C) is a focal neurodegenerative disease with a genetic predisposition and autoimmune etiology; the pathogenesis of narcolepsy without cataplexy (Nw/oC) is less clear. One hundred and forty eight patients underwent clinical face-to face interviews, polysomnography, multiple sleep latency testing and HLA-DQB1*0602 typing. The cohort was divided into four age groups: children and adolescents under 19 years (N = 31), adults aged 20-39 years (N = 51), 40-59 years (N = 28) and over 60 years (N = 38). N-C was found in 93 adults (79.5 %) compared with 16 pediatric patients (51.6 %) (p < 0.01), suggesting that at least some of the children were candidates for developing cataplexy in the future. Statistical evaluation showed an increasing age-related proportion of associated sleep disorders-obstructive sleep apnea, periodic leg movements and restless leg syndrome (p < 0.001). Nw/oC patients showed sleep comorbidities less frequently than N-C group. A close connection with N-C was found particularly in REM behavior disorder (RBD) (p < 0.05). RBD affected a third of the patients in the youngest as well as in the oldest groups. However, association with other sleep disorders had no significant effect on nocturnal sleep (with the exception of obstructive sleep apnea), and the sleep comorbidities under study had no noticeable effect on daytime sleepiness.
Keywords: senioři; Cross-Sectional Studies; Sleep Wake Disorders; senioři nad 80 let; Restless Legs Syndrome; narkolepsie; poruchy spánku a bdění; syndrom neklidných nohou; mladiství; Cohort Studies; Middle Aged; mužské pohlaví; stadia spánku; Polysomnography; průřezové studie; Adult; mladý dospělý; Adolescent; kohortové studie; dítě; Sleep Stages; Child; věkové faktory; Aged, 80 and over; Young Adult; Narcolepsy; ženské pohlaví; Humans; polysomnografie; lidé středního věku; REM Sleep Behavior Disorder; Age Factors; dospělí; Female; Aged; porucha chování v REM spánku; lidé; Male